Growth performance and nutrient digestibility of grower–finisher pigs fed corn DDGS-soybean meal-based diets supplemented with a combination of protease and multi-strain Bacillus-based direct-fed microbial - Rajaei-Sharifabadi, Hossein; Seradj, Ahmad Reza; Lashkari, Saman; Velayudhan, Deepak E.; Vinyeta, Ester; Woyengo, Tofuko Awori (Frontiers in Animal Science, 2025)
Energy and nutrient availability in corn DDGS for pigs is partly limited by complex interactions between fiber and protein of the corn DDGS. Supplemental direct fed microbials (DFM) and protease can potentially improve energy and nutrient availability in corn DDGS-based diets for pigs. This study determined the effects of supplementing a corn DDGS-soybean meal (SBM)-based diet with a combination of protease and Bacillus-based DFMs on the growth performance and apparent total tract digestibility (ATTD) of nutrients in pigs. Eighty pigs (initial BW = 29.2 kg) housed in 20 pens were fed two diets (10 pens per diet), which were a corn DDGS-SBM-based diet without or with a combination of Bacillus subtilis protease at 5,000 U/kg and three-strain Bacillus-based DFMs at 1.5 × 105 CFU/g. The basal diet contained phytase at 750 FTU/kg and was formulated to meet the nutrient recommendations for grower–finisher pigs except for NE, Ca, and P contents, which were lower than the recommendations by 0.209 MJ/kg, 0.9 g/kg, and 0.9 g/kg, respectively. The diets were fed in three phases based on BW: phase 1 from 30 to 55 kg, phase 2 from 55 to 75 kg, and phase 3 from 75 to 100 kg. Growth performance was determined by phase, whereas the ATTD of nutrients was determined at the end of phase 1. Protease and DFM supplementation increased (P < 0.05) the ATTD of gross energy, nitrogen, and P by 8.0%, 10.3%, and 15.5%, respectively, but did not affect BW gain and feed intake. In conclusion, adding protease and DFMs to the corn-DDGS-SBM-based diet increased nutrient digestibility but did not affect the growth performance of pigs, implying that the basal diet was not deficient in energy. Thus, basal diets with appropriate low energy values should be developed to optimize the utilization of protease and DFMs in diets for pigs.